Cytotoxic and Genotoxic Effects of the Cold Aqueous Extract of Glycyrrhiza glabra Roots on MCF-7 Breast Cancer Cells and REF Normal Cells in Vitro (Medical Forum Monthly, 2025)
Objective: To evaluate the cytotoxic and genotoxic effects of the cold aqueous extract of Glycyrrhiza glabra roots on MCF-7 breast cancer cells and REF normal cells in vitro.Study Design: Experimental studyPlace and Duration of Study: This study was conducted at the Al-Nahrain University Biotechnology Research Centre from 22nd December 2024 to 20th March 2025.Methods: Glycyrrhiza glabra extract was administered to MCF-7 breast cancer cells at different concentrations (70, 140, 210, 280, and 350 μg/ml) for 24, 48, and 72 hours. The embryonic fibroblast cells were treated 72 hours. Cell viability, IC50 values, and deoxyribonucleic acid damage was assessed using the comet assay.Results: This extracts reduced MCF-7 cell proliferation time- and dose dependently at 350 μg/ml inhibition rates was significantly (p<0.05): 77.778% (24 h), 79.349% (48 h), and 87.262% (72 h). The IC50 of embryonic fibroblast cells was 5.59 mg/ml after 72 hours, demonstrating selective susceptibility. In the comet test, MCF-7 cells treated with increasing extract concentrations demonstrated moderate and severe DNA damage after 72 hours.Conclusion: Gglycyrrhiza glabra root cold aqueous extract is dose and time-dependently cytotoxic and genotoxic to MCF-7 breast cancer cells but not normal fibroblast cells.